Nitrogen and carbon isotopes in fossil aquatic ecosystems - Hellawell, Joanne (Trinity College (Dublin, Ireland). Department of Geology, 2009)
In a modem ecosystem, the trophic level of organisms can be distinguished on the basis of their nitrogen and organic carbon isotopic signature (DeNiro & Epstein 1978 and 1981). Due to fractionation during the assimilation of food and the creation of new body tissues, these stable isotopes reflect the diet of each consumer, thus their relative position in a food web can be inferred based on their biochemistry. δ15N is considered to be a direct indicator of trophic level, whereas δ13Corg is thought to reflect the influence of different potential food sources (e.g. Minagawa & Wada 1984; Hecky & Hesslein 1995). These stable isotopes have also been used to infer the feeding habits of prehistoric animals, in particular in the interpretation of diet of early humans from archaeological sites (e.g. Drucker & Bocherens 2004; Hedges & Reynard 2007). The purpose of this study was to investigate whether the isotopes of δ15N and δ13Corg could be applied to a much older fossil ecosystem to distinguish the community structure and palaeoecology. The Eocene fish from the Green River Formation lagerstatte in SW Wyoming, USA, were chosen as the experimental fauna. Although exceptional preservation does not necessarily imply preservation of the original isotopic values, these fish are thought to have been subject to little diagenetic change (Norris et al 2000). Regular mass mortality horizons occur throughout the stratigraphy, representing census assemblages of co-existing taxa in a tightly constrained temporal framework, thus presenting an ideal testing ground for this study.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin